Prenatal diagnosis and perinatal outcome of congenital dacryocystocele: a large case series - Li, Sheng-li; Luo, Guo-yang; Tian, Xiao-xian; Yu, Rong; Norwitz, Errol R.; Qin, Feng-zhen; Wen, Hua-xuan; Bi, Jing-ru; Lin, Xiao-ying; Zhong, Xiao-hong (Prenatal diagnosis, 2015)
Objective To describe the incidence, prenatal diagnosis, and perinatal outcome in fetuses with congenital dacryocystocele. Methods All cases of congenital dacryocystocele diagnosed by prenatal ultrasound were identified using an established perinatal database. Prenatal ultrasound images were reviewed, and perinatal outcome was ed from the medical records. The correlation between the cyst size, gestational age, and prenatal and neonatal outcome was analyzed. Results The overall incidence of fetal dacryocystocele was 0.016% (75/456,202). Fifty‐three cases (70.7%) had unilateral, and 22 (29.3%) had bilateral lesions. Lesions were seen more commonly among female fetuses with a female : male ratio 1.48 : 1. The average diameter of cysts size was 6.9 ± 1.9 mm (3.3–11 mm). There was a direct correlation between cyst size and gestational age. Among the 75 cases, 8 were lost to follow‐up, 3 underwent elective termination of pregnancy. 58 resolved spontaneously before birth, and 6 were confirmed at birth. Two developed neonatal infection requiring antibiotic treatment. All 6 cases confirmed at birth resolved without surgical resection. Conclusions Congenital dacryocystocele can be diagnosed by prenatal ultrasound. Such lesions typically resolve spontaneously in utero or in the early neonatal period. Thus, it should be considered as a developmental variant rather than a structural birth defect. © 2014 John Wiley & Sons, Ltd. What's already known about this topic? Dacryocystocele is a rare congenital condition characterized by one or more facial cysts as a result of obstruction of the lacrimal and/or nasolacrimal duct, which may become complicated by infection and require surgical intervention. What does this study add? This paper represents the largest series of dacryocystoceles diagnosed prenatally and suggests that such lesions typically resolve spontaneously in utero or in early neonatal period without surgical intervention. Dacryocystocele should be considered as a developmental variant rather than a structural birth defect.